You Only Die Once: Calvinist Dying and the Senses in Lille and Tournai During the Dutch Revolt - Deschryver, Louise (Early Modern Low Countries, 2020)
Many historical studies have been published on how Lutheran and Calvinist teachings about death, salvation, and the Last Judgement differed from Catholic tradition. However, historians of the Reformation and death have not yet fully addressed how these diverging dying paradigms affected sensory practices of dying and burying among the laity. This article introduces attention to the senses in Catholic and Calvinist death rituals in the sixteenth-century Low Countries. It argues that how to use the body and the senses was at the heart of a chilling choice on which confessional death to die. By studying Catholic and Calvinist death rituals in sixteenth-century Lille and Tournai – French-speaking frontier cities close to hotbeds of Calvinism –  this article contributes to our understanding of sensory community and identity formation on a local level during the Reformation.